Quantitative Evaluation of Bacteria Adherent and in Biofilm on Single-Wall Carbon Nanotube-Coated Surfaces - Fabrizio Pantanella; Francesca Berlutti; Daniele Passeri; Daniela Sordi; Alessandra Frioni; Tiziana Natalizi; Maria Letizia Terranova; Marco Rossi; Piera Valenti (Interdisciplinary Perspectives on Infectious Diseases)
Biofilm is a common bacterial lifestyle, and it plays a crucial role in human health, causing biofilm-mediated infections. Recently, to counteract biofilm development, new nano-structured biomaterials have been proposed. However, data about the antibacterial properties of nano-structured surfaces are fragmentary and controversial, and, in particular, the susceptibility of nano-structured materials to colonization and biofilm formation by bacterial pathogens has not been yet thoroughly considered. Here, the ability of the pathogenic Streptococcus mutans and Pseudomonas aeruginosa to adhere and form biofilm on surfaces coated with single-wall carbon nanotubes (SWCNTs) was analyzed. Our results showed that the surfaces of SWCNTs-coated glass beads (SWCNTs-GBs) were colonized at the same extent of uncoated GBs both by S. mutans and P. aeruginosa. In conclusion, our results demonstrate that single wall SWCNTs-coated surfaces are not suitable to counteract bacterial adhesion and biofilm development.